Measuring neurodevelopmental effects of polygenic risk for Alzheimer's disease via longitudinal study of brain and cognitive variables in periadolescent children: Genetics/genetic factors of Alzheimer's disease. (7th December 2020) - Warren, David E.; Phipps, Connor J.; Eckel, Medea; Rangel, Anthony; Heller, Abi M.; Maerlender, Arthur C.; Phatak, Vaishali S.; Cramer, Justin A.; Blair, James; Murman, Daniel L.; Smith, Shelley D.
Abstract: Background: Individual variability in Alzheimer's disease (AD) risk is greatly affected by genetic factors, and those factors may exert early influence on brain development. Specifically, genetic/genomic AD risk factors may bias brain development toward vulnerability to late onset AD. We are conducting a five‐year study (funded by the National Institute on Aging) to test the hypothesis that polygenic AD risk alters neurodevelopment of brain systems most affected by AD in ways that increase vulnerability to late‐onset AD. If true, then properties of AD‐vulnerable brain structures (e.g., hippocampus) and AD‐vulnerable brain networks (e.g., default mode network) will vary with polygenic AD risk even during youth. Here, we describe our study aims, approach, and predictions. Methods: We have implemented our project as the Polygenic Risk of Alzheimer's disease in Nebraska Kids (PRANK) study. The PRANK study will measure neurodevelopmental effects of AD polygenic risk scores (ADPRS) with three aims: 1) measure effects of ADPRS on development of AD‐vulnerable brain regions; 2) quantify how ADPRS affects development of functional brain networks vulnerable to AD; and 3) evaluate effects of ADPRS on development of AD‐vulnerable cognitive abilities. To address these aims, we are developing a new dataset which combines neuroimaging (brain structure/function), neuropsychology (cognition), and genomics (ADPRS) in a longitudinal design. Our study is currently enrolling healthy youth age 8‐13 years; our multi‐year recruitment goal is N = 270. Participants will return for follow‐up two years after initial participation. Results: Our study is ongoing, but we will discuss our design and preliminary findings. We predict that higher ADPRS in otherwise typically developing youth will be associated with: 1) smaller hippocampal volume and decreased cortical thickness in AD‐related ROIs; 2) lower connectivity in functional brain networks and less brain activity in memory tasks; 3) lower scores on measures of AD‐related cognitive abilities (e.g., memory and executive functions) after accounting for IQ. Conclusions: Findings from the PRANK study will improve the field's understanding of how developmental effects of ADPRS relate to clinical and epidemiological challenges of AD. Measuring how genetic/genomic factors associated with late‐onset AD affect brain development will elucidate lifelong trends for AD risk while highlighting new opportunities for early intervention.